Nomadic culture and chivalric tradition (XIX-early XX centuries) - E.A. , Azi; S.M. , Aralbay; K.I. , Kurazova (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
It is true that there are traditions, customs, rituals, national games, traditional art, and musical heritage that distinguish one nation from another and make it clear that the nation is a nation. In this respect, the Kazakh people are not an exception. This rich spiritual, cultural and literary heritage of the Kazakh people testifies to the fact that this people is a long-standing ancient tribe, a follower of bagzi nomads who are rooted from the depths of centuries. It is a fact that at all times every nation had its own values and culture, which poured into the minds of future generations, made them heroes, men who protect their country and land. After all, the future of the country is necessary for the development of the future of this nation, to radiate into the minds of generations, mixing the essence of youth, national psychology with the sacred heritage of the ancestors, that is, identity and morality. And today it is one of the most important things for the spirituality of the Kazakh people. We think that it is urgent to popularise the heritage and works of our historical figures, who are scattered every time in the steppe, who have a strong memory, who gave their lives for the future of the nation, and thus educate future young people in the national direction. For this reason, it is worth popularising the propaganda of the words of our sages and poets, instilling them in the minds of young people as much as possible, combining them with traditions and upbringing from the cradle. It is clear that the traditions and customs of a fundamental country in Central Asia drag on to ancient times. So, the culture also dates back to those times. Therefore, the goal is to combine the Customs and traditions of the Kazakh people, which differ from other ethnic groups, with their culture. The article analyses the culture, art, multifaceted artists of the Kazakh people as a unique artistic phenomenon, discusses examples of traditional art of nomadic culture, whose general and distinctive manifestations reflect the historical path of the Kazakh people.